Effectiveness of Rules and Regulations on Grade 12 HUMSS Strand Student in Bestlink College of the Philippines: An Assessment (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
Students are the key stakeholders and most essential resources in education. Students should be directed to exhibit an acceptable attitude and behavior within and outside the school. The school management specifies rules and regulations to guide the activities of members of the educational institution, thereby ensuring an organized and peaceful school environment and maintaining law and order. This study aimed to assess the effectiveness of rules and regulations on Grade 12 Humanities and Social Sciences (HUMSS)Strandstudents at Bestlink College of the Philippines. This research utilized a quantitative method of research. Descriptive design was also used to describe the situation of this study. The researcher used a stratified sampling technique to select the respondents to determine the effects of rules and regulations on the academic performance of Grade 12 HUMSS Strandstudents’grade. A questionnaire was the instrument used to obtain the data of the respondents. The questionnaire consisted of questions that were primed, hand-written, and typed in a definite order on a form or set of forms. The results of the study showed how rules and regulations affect the academic performance of Grade 12 HUMSS stand students. In terms of attendance (61%), behavior (83%), wearing complete school uniform (72%), charging (69%), and having a proper haircut (66%), the majority answered strongly agree (percentage in each variable). In academic performance or class discussions, 60% of the respondents agreed on this matter. Most respondents have the perceptions that individually, they occasionally break school rules and do not follow regulations. The respondents believed that other students in their respective schools also occasionally break school rules and do not follow regulations. The majority of respondents have been punished several times after breaking school rules and regulations. The researchers recommended that school rules and regulations must be emphasized and given enough awareness to create harmony and cooperation among students and lead more students to become good citizens.
Keywords: resource, education